2012
DOI: 10.1155/2012/621496
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Catheter (PAC) Accuracy and Efficacy Compared with Flow Probe and Transcutaneous Doppler (USCOM): An Ovine Cardiac Output Validation

Abstract: Background. The pulmonary artery catheter (PAC) is an accepted clinical method of measuring cardiac output (CO) despite no prior validation. The ultrasonic cardiac output monitor (USCOM) is a noninvasive alternative to PAC using Doppler ultrasound (CW). We compared PAC and USCOM CO measurements against a gold standard, the aortic flow probe (FP), in sheep at varying outputs. Methods. Ten conscious sheep, with implanted FPs, had measurements of CO by FP, USCOM, and PAC, at rest and during intervention with inot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…An increase in SV of 10 to 15% is used to define fluid responsiveness [66]. This threshold is significantly below the ability of the PAC to detect a change in CO [22]. In addition to its inability to determine fluid responsiveness the CO itself has very little utility in guiding patient management.…”
Section: Reviewmentioning
confidence: 99%
“…An increase in SV of 10 to 15% is used to define fluid responsiveness [66]. This threshold is significantly below the ability of the PAC to detect a change in CO [22]. In addition to its inability to determine fluid responsiveness the CO itself has very little utility in guiding patient management.…”
Section: Reviewmentioning
confidence: 99%
“…Percentage error was 91.7%. Baseline SVI appeared to be similar, but PRAM SVI was systematically greater than bioreactance thereafter, with the highest gap after the fluid loading phase: 13 (12)(13)(14)(15)(16)(17)(18) mlÁm À2 vs. 23 (19)(20)(21)(22)(23)(24)(25) mlÁm À2 , respectively, P = 0.0013. A multivariable regression model showed that a significant independent inverse correlation with patients' body weight predicted the CI difference between the two methods after fluid challenge (b coefficient À0.12, P = 0.013).…”
Section: Discussionmentioning
confidence: 92%
“…None of these methods is currently validated and/or recommended during pediatric cardiac surgery. Furthermore, as evidenced by a recent research where thermodilution CO was compared with surgically implanted ultrasonic flow probes in an ovine model , the PAC showed to be unreliable for detection of CO changes <30–40%. Critchely et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, this methodology has itself been challenged and USCOM precision is comparable to other non-invasive CO measurement techniques [17]. The precision of PAC itself is increasingly being questioned [31]. USCOM has been compared to echocardiography Doppler measures, 'estimated' (USCOM) and 'measured' left ventricular outflow tract diameters were not significantly different, but USCOM consistently 'overestimated' CO, particularly in children with septic shock [29].…”
Section: Doppler Phenomenonmentioning
confidence: 99%